2001
DOI: 10.1086/323979
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Manifestations of DisseminatedMycobacterium aviumComplex Infection in South Africans with Acquired Immunodeficiency Syndrome

Abstract: In a sample of 100 hospitalized human immunodeficiency virus-seropositive black South African patients with CD4 cell counts of <100 cells/mm(3), the point prevalence of disseminated Mycobacterium avium complex infection was 10%, in contrast with other African studies that report that the infection is uncommon. The point prevalence of Mycobacterium tuberculosis was 54%. The clinical and laboratory features of these patients were largely unhelpful in detecting M. avium complex; the BACTEC blood culture (Becton D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…It has been recognised as an important opportunistic infection in countries in sub-Saharan Africa in studies employing mycobacterial blood cultures. [5][6] It is associated with a high mortality in the ART era with only 30% of such patients alive beyond 2 years. 7 Treatment failure is common, reasons including drug toxicity, inadequate serum levels and development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recognised as an important opportunistic infection in countries in sub-Saharan Africa in studies employing mycobacterial blood cultures. [5][6] It is associated with a high mortality in the ART era with only 30% of such patients alive beyond 2 years. 7 Treatment failure is common, reasons including drug toxicity, inadequate serum levels and development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In 37 patients dying beyond one year on ART, virological failure was present in 11 (30%), and non-HIV-related causes of death occurred in 10. The main causes were acute sepsis (6), tuberculosis (7) and chronic medical conditions (5). Initiating ART at higher CD4 counts should reduce early mortality.…”
Section: Profile Of Cause Of Death Assigned To Adults On Antiretrovirmentioning
confidence: 99%
“…However, pulmonary disease may also be due to non-tuberculous mycobacteria (NTM), particularly in HIV-infected patients. Several recent studies from sub-Saharan Africa suggest the prevalence of NTM disease may be higher than previously recognized [1][4]. One study has also reported isolating NTM species from water and soil in Uganda [5].…”
Section: Introductionmentioning
confidence: 98%
“…More recently, research has been initiated in African and East Asian countries (1)(2)(3)(4)(5). There have been no recent reports on isolation and clinical relevance of NTM on the Arabian Peninsula.…”
mentioning
confidence: 99%